Per una rilettura di A Liuba che parte. Note in margine - Colonnello, Pio (Bollettino Filosofico, 2017)
The essay is based on an interpretation of Montale's poetry. A fundamental Leitmotive attempts to locate the pathways that allow the dialogue between Philosophy and Poetry. Therefore, the question is if this poem by Montale could correspond, as argued by the structuralist critique, to a "birthday card", a "gallant tribute", an "opera aria", or rather does not the sober and serious tone prevail  that accompanies the departure of a friend, caused by the racial laws. Does the philological structural analysis – which openly disregards the content and identifies in this poem the structure of the "Ballad", the medieval poem known as "departure" –, really restore to us what the poet wanted to say on the occasion of an untoward event? The poem, after all, is a "greeting card" and suggests the idea of a "cantatina", or rather, through a "fragment", an unusual perspective, does it track the merciless portrait of an era in flames ?